Phenolics Compounds And Antioxidant Activities From Optimized Pheonix Dactylifera Extract Using Response Surface Methodology - Siti Salwa Abd Gani; Nur Asyiqin Binti Ramli; Mohd Izuan Effendi Halmi; Salina Mat Radzi (INSTITUT KIMIA MALAYSIA, 2024)
Indexed by Scopus